Analysis Of Heat Effect Of Fuel Made Of Palm Fiber And Kernel Shell On The Efficiency Or Water Pipes Boiller - Nasikin R F (Bandar Lampung University (UBL), 2017)
boiler is a steam generator which is composed of a combination of complex form of economizer,boiler, heating up, reheat, and initial air heater. Fiber and shells is one example of a solid boiler material. Each fuel boiler has a value LHV different. Value Low Heating Value hightest by fuel boiler shells kinds pure with a value 44184.391 Kcal / Kg, while for LHV fuel value of the smallest boiler boiler fuel owned by pure fiber types by value 29959.325 Kcal / Kg. , Obtained with the use of boiler types of pure and mixed fiber B is 80% + 20% fiber shell boiler produce the highest efficiency with the value of 83.6236948% the number of different fuels to fuel pure fiber as fiber spent 129.1945968 Kg / H while mixture B spent 108.788094 kg / H